In Vitro Development Of Holstein And Japanese Black Breeds Embryo - A. Boediono; T. Suzuki (Media Veteriner, 1996)
Two experiments were conducted with 3,457 oocytes, aspirated from the ovaries of slaughtered Holstein and Japanese Black breeds cows to compare the use of superovulatedcow serum (SCS) and fetal calf serum (FCS) supplementation into medium for in vjtro development (experiment I) and the effect of different source of oocytes (experiment II). Theendpoint was development to cleavage on day 2 and to blastocyst up to day 9 after msermnabon. In experiment I, oocytes were matured and cultured m vltro (after fertilization)in TCM-199 supplemented with 5% SCS or 5% FCS. The cleavage rate of zygotes cultured in medium supplemented with 5% SCS was higher (P